Pengaruh Kompetensi, Kompensasi dan Budaya Kerja terhadap Kinerja Karyawan pada PT. Hutan Sawit Lestari (Journal of Environment and Management, 2020)
The management of PT Hutan Sawit Lestari (HSL) in Kotawaringin Timur Regency reported a decrease in the performance of their employees. The preliminary study indicates the influence of competence, compensation and works culture in the company environment on the decreasing performance. This study aims to confirm the influence of the three variables on the performance of employees of PT. HSL. Statistical methods and Structure Equation Model analysis based on Partial Least Square (SEM-PLS) are used to find out the relationship between variables. The data collected through observation, questionnaires, literature study or documentation. The results show that the three independent variables, namely competence, compensation, and work culture, significantly influence the dependent variable or performance. Finally, we offer a set of suggestions for boosting the workers' performance.